Poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) copolymer beads as support for covalent immobilization of L-aminoacylase - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Nene, Sanjay N. (Reactive & Functional Polymers, 2012)
Porous epoxy-activated copolymer beads were synthesized as support for the covalent immobilization of Aspergillus melleus L-aminoacylase. Here, a series of copolymer bead were synthesized using either glycidyl methacrylate (GMA) or ally] glycidyl ether (AGE) as monomer units and ethylene glycol dimethacrylate (EGDM) as cross-linking agent. The effect of monomer used and the effect of amount of cross-linking agent on covalent immobilization of aminoacylase were studied. Furthermore, the effect of porogen on immobilization of aminoacylase was also evaluated. AGE-co-EGDM copolymer beads gave higher binding of aminoacylase than GMA-co-EGDM copolymer beads. AGE-co-EGDM copolymer beads synthesized with lauryl alcohol as porogen and having 150% cross-linked density (i.e. AGE-(L)-150) gave maximum enzyme binding. Under optimum conditions, AGE-(L)-150 copolymer beads gave about 130 U/g of aminoacylase activity which corresponds to 72.24% of activity yield. Immobilized aminoacylase showed a broader pH, higher temperature and extended storage stability. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization; Epoxy-activated support; L-Aminoacylase